Monitoramento e acionamento remoto da movimentação e arrefecimento de painéis fotovoltaicos para maximização da potência e eficiência - Miotto, Maicon (2019)
The world's electricity consumption increases every day along with concerns about the environment. In order to supply the increase in the demand for electric power in Brazil there has been in recent years a great expansion in the generation of renewable sources of electric energy. These sources are mainly provided by photovoltaic panels (PVs) and wind turbines associated with a reduction in the number of new hydroelectric power plants. In this sense, a study aimed at the application and use of photovoltaic panels has great importance. This is relates to the increased power and efficiency of PV panels that can be optimized by tracking systems, solar concentrators, cooling mechanisms and heat utilization. This dissertation is the development of a systematic control and monitoring standard for photovoltaic plants that allows experimental studies on the radiation tracking, solar concentration and cooling of photovoltaic panels aiming at maximizing the resulting power and efficiency via a remote communication channel. In this development was used as a prototype the experimental PV power plant of CEESP/UFSM. For this research, the communication and actuation system was designed in a modular way with the use of microcontrollers in charge of five different functions. The first one is responsible for measuring the electrical power generation, the second is controlling the panel cooling down, the third and fourth controlled the panel movements in two distinct axes and the fifth makes the acquisition of meteorological data. The microcontrollers are connected to a communication network and a master microcontroller that coordinates the information flow with the necessary controls for this diversified photovoltaic plant. The monitoring of the energy generation variables in the PV panels, such as voltage, current and temperature, showed a very acceptable approximation rate of around 97%. The voltage and current measurements had very low errors, less than 0.5%. In the movement, the errors of performance were also quite reduced, of the order of 0.2 ° to 0.3 °. For the cooling of the PV panels using geothermal energy and closed circulation through a water reservoir, the temperature remained very stable in the PV plate, around 35 to 40 °C. Finally, practical tests were done to compare some configurations, such as fixed photovoltaic panels and with manual tracking. Photovoltaic panels with two-axis tracking gears achieved a power generation efficiency 32% higher than that obtained in the reference PV panel with an optimal fixed position at 30° thereby demonstrating the operation effectiveness of this proposal.